Methods and Protocols for Reliable Electrochemical Testing in Post-Li Batteries (Na, K, Mg, and Ca) - Dugas, Romain (Chem Mater, 2019)
[Image: see text] While less mature than the Li-ion battery, technologies based on Na, K, Mg, and Ca are attracting more and more attention from the battery community. New material (cathode, anode, or electrolyte) testing for these post-Li systems commonly involves the use of an electrochemical setup called a half-cell in which metal counter and reference electrodes are used. Here we first describe the different issues that become critical when moving away from Li with respect to the cell hardware (cell design, current collector, separator, insulator) and the nature of the counter and reference electrodes. Workarounds are given, and a versatile setup is proposed to run reliable electrochemical tests for post-Li battery materials in general, in a broad range of electrolyte compositions.